2003
DOI: 10.1177/0146167203029006007
|View full text |Cite
|
Sign up to set email alerts
|

A Four-Component Model of Procedural Justice: Defining the Meaning of a “Fair” Process

Abstract: Two studies test the prediction of the four-component model of procedural justice that people evaluate the fairness of group procedures using four distinct types of judgment. The model hypothesizes that people are influenced by two aspects of the formal procedures of the group: those aspects that relate to decision making and those that relate to the quality of treatment that group members are entitled to receive under the rules. In addition, people are hypothesized to be separately influenced by two aspects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
305
1
12

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(324 citation statements)
references
References 22 publications
6
305
1
12
Order By: Relevance
“…Honesty, fairness, neutrality (as well as other characteristics like courage, determination, humility, self-control, and so on), are commonly seen as aspects of moral character or virtue (Cen & Yu, 2014;Wren, 2014). Although fairness and neutrality/bias are more typically viewed as components of the broader construct of procedural justice (Blader & Tyler, 2003;Burke & Leben, 2007, little research to date has investigated how such constructs relate to Mayer et al's (1995) three constructs (see Colquitt & Rodell, 2011, for a rare such investigation).…”
Section: Trust Versus Trustworthinessmentioning
confidence: 99%
“…Honesty, fairness, neutrality (as well as other characteristics like courage, determination, humility, self-control, and so on), are commonly seen as aspects of moral character or virtue (Cen & Yu, 2014;Wren, 2014). Although fairness and neutrality/bias are more typically viewed as components of the broader construct of procedural justice (Blader & Tyler, 2003;Burke & Leben, 2007, little research to date has investigated how such constructs relate to Mayer et al's (1995) three constructs (see Colquitt & Rodell, 2011, for a rare such investigation).…”
Section: Trust Versus Trustworthinessmentioning
confidence: 99%
“…Note. The listed criteria reflect work by Leventhal (1980), Tyler (1990), Colquitt (2001) and Blader & Tyler (2003). …”
Section: Resultsmentioning
confidence: 99%
“…There is substantial evidence that leader behavior that violates procedural fairness criteria lowers the efforts that the individual puts into communal efforts. In particular, studies have demonstrated that procedural fairness is an important component in inducing "organizational citizenship" (Folger & Konovsky 1989 ;Sweeney & McFarlin 1993;Tyler & Degoey 1995;Blader & Tyler 2003). In the workplace, for example, people experiencing fair procedures are more committed to the company and its goals (Lavelle et al 2009), report higher job satisfaction (Pillai et al 1999), and are less inclined to switch jobs (Daileyl & Kirk 1992).…”
Section: Procedural Fairness As a Diagnostic Toolmentioning
confidence: 99%
“…For instance, actual citizenship standing may feel somewhat compromised when authorities performing policing services related to national security (e.g., airport and border security personnel) fail to be attentive to relational, treatmentoriented concerns. Perceptions of disrespect, lack of trust and bias all contribute to evaluations of out-group status relative to administering authorities (Blader and Tyler 2003;Smith et al 1998;Tyler 1989), which, in this context, may be equatable to sentiments of flawed citizenship relative to the more privileged status of persons whose treatment connotes in-group membership with administering authorities.…”
Section: Relational Concerns Group Membership and Surveilled Subjectmentioning
confidence: 99%